Karakteristik Antropometri Anak dan Kejadian Underweight di Kelurahan Bugel, Karawaci, Tangerang - Dara Avindharin, Pundra; Nurul Hikmah, Agnia; Sari Nasrianti, Citra (Jurnal Nusantara Madani, 2023)
Background: Underweight is a condition where a child's weight is too low for their age. Underweight in children leads to physical and mental health disorders, behavioral issues, and cognitive impairments. One of the factors influencing underweight occurrence is the anthropometric characteristics at birth, such as Birth Weight and Birth Length. This study aims to determine the Anthropometric Characteristics of Children and the Incidence of Underweight in Bugel Urban Village, Karawaci, Tangerang. Subjects and methods: This cross-sectional study included children aged 0-60 months in Bugel Urban Village, Tangerang City. The sample comprised 100 respondents selected through purposive sampling. Data were collected using a questionnaire through interviews. Univariate analysis with frequency distribution and bivariate analysis using the Chi-Square test were employed for data analysis.Results: The study found that Birth Weight had a significant association with underweight incidence (p value = 0.034), and Birth Length also had a significant association with underweight incidence (p value = 0.001).Conclusion: Children with Birth Weight <2500 grams are 7.545 times more likely to experience underweight compared to those with Birth Weight >=2500 grams, and children with Birth Length <48 cm are 8.566 times more likely to experience underweight compared to those with Birth Length >=48 cm. Keywords: Underweight, Child Gender, Child Age, Low Birth Weight (LBW), and Low Birth Length (LBL)